Preparation method of composite solid electrolyte and composite solid electrolyte prepared by same

By using PEO-type copolymers and ceramic compounds with crosslinkable functional groups in the composite solid electrolyte and using vapor deposition technology, the problem of insufficient ionic conductivity of composite solid electrolytes in the prior art is solved, and the high ionic conductivity and mechanical properties are improved, and electrolytes suitable for all-solid state batteries are improved.

CN119923736APending Publication Date: 2025-05-02LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380065456.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-12
Filing Date
2023-10-13
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

There are limitations in the improvement of ionic conductivity in existing composite solid electrolytes, especially when using highly crystalline polymers such as polyethylene oxide (PEO), the mobility of lithium ions is limited and it is difficult to meet the needs of high ionic conductivity.

Method used

By preparing a mixed solution containing PEO-type copolymers and ceramic compounds containing crosslinkable functional groups, a composite solid electrolyte layer is formed using an unwinding machine and vapor deposition technology to ensure uniform dispersion of the ceramic compounds and improve the chain mobility of the polymer chain through vapor deposition of polar solvents.

Benefits of technology

It achieves the improvement of the ionic conductivity and mechanical properties of the composite solid electrolyte without deformation or damage to the polymer chain, and can be produced on a large scale, suitable for all-solid state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923736A_ABST
    Figure CN119923736A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a composite solid electrolyte and a composite solid electrolyte prepared by the same. The preparation method comprises the following steps: (S1) preparing a mixed solution containing a PEO (polyethylene oxide) copolymer containing a crosslinkable functional group and a ceramic compound; (S2) unwinding the substrate using an unwinding machine and supplying it to the transfer path; (S3) coating the mixed solution on the base material to form a coating film; (S4) transferring the substrate on which the coating film is formed to a drying unit and drying the substrate to form a polymer film; (S5) transferring the polymer film to a vapor deposition part and vapor depositing a polar solvent to form a composite solid electrolyte layer; and (S6) winding and recovering the substrate comprising the composite solid electrolyte layer using a rewinding machine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0132766 filed on October 14, 2022, and Korean Patent Application No. 10-2023-0136063 filed on October 12, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present invention relates to a method for preparing a composite solid electrolyte and a composite solid electrolyte prepared thereby. Background Art

[0004] Lithium-ion batteries using liquid electrolytes have a structure in which the negative electrode and the positive electrode are defined by a separator, so when the separator is damaged by deformation or external impact, a short circuit may occur, causing dangers such as overheating or explosion. Therefore, it can be said that the development of a solid electrolyte that can ensure safety is a very important issue in the field of lithium-ion secondary batteries.

[0005] The advantages of lithium secondary batteries using solid electrolytes are that they have enhanced safety, prevent leakage of electrolytes to improve battery reliability, and facilitate the manufacture of thin batteries. In addition, lithium metal can be used as a negative electrode to increase energy density. Therefore, in addition to compact secondary batteries, it is also expected to be applied to high-capacity secondary batteries for electric vehicles and has attracted much attention as a next-generation battery.

[0006] Among solid electrolytes, polymer solid electrolytes may include polymer materials made of ion conductive materials, or inorganic materials such as oxides or sulfides having ion conductive properties. In addition, composite polymer solid electrolytes that are mixtures of polymer materials and inorganic materials have been proposed.

[0007] This conventional composite polymer solid electrolyte is prepared by dispersing oxide ceramic powders, etc. in a polymer matrix, and has the advantages of higher stability than existing liquid electrolytes and higher ionic conductivity than polymer solid electrolytes, but it is difficult to meet basic prerequisites, such as improving the dispersibility of ceramic particles such as oxides in the polymer matrix and optimizing the physical properties of the polymer matrix used. In particular, there is a limitation in that it is difficult to use highly crystalline polymers such as polyethylene oxide (PEO) to prepare a composite solid electrolyte with improved ionic conductivity. In other words, the high crystallinity of the polymer hinders the chain mobility of the polymer chain, thereby limiting the movement of lithium ions in the polymer solid electrolyte, which makes it difficult to improve the ionic conductivity of the polymer solid electrolyte.

[0008] In order to overcome this limitation of conventional composite solid electrolytes, a technique has been developed to modify the structure of crystalline polymers or add separate plasticizers to polymers, thereby improving the mobility of polymer chains and enhancing the ionic conductivity of composite solid electrolytes. However, it is difficult to increase the ionic conductivity of solid polymer electrolytes prepared by using such structural deformation of polymers and addition of plasticizers to a level above 1 mS / cm.

[0009] Therefore, in addition to polymer solid electrolytes prepared by modifying the structure of the polymer, adding a separate plasticizer, or immersing the solid electrolyte in a liquid electrolyte, it is necessary to develop a technology related to a method for preparing a composite solid electrolyte as a pure solid electrolyte for an all-solid-state battery, which can improve the ionic conductivity of the electrolyte and enable a continuous process.

[0010] [Prior art literature]

[0011] [Patent Document]

[0012] (Patent Document 1) Japanese Patent Application Publication No. 1994-124713 Summary of the invention

[0013] [Technical issues]

[0014] An object of the present disclosure is to provide a method for preparing a composite solid electrolyte and a composite solid electrode prepared therefrom, the method improving ion conductivity and realizing a continuous process.

[0015] [Technical solution]

[0016] According to one embodiment of the present disclosure, a method for preparing a composite solid electrolyte is provided, the method comprising the following steps: (S1) preparing a mixed solution comprising a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group and a ceramic compound; (S2) unwinding a substrate using an unwinder and supplying it to a conveying path; (S3) applying the mixed solution to the substrate to form a coating film; (S4) transferring the substrate having the coating film formed thereon to a drying section and drying it to form a polymer film; (S5) transferring the polymer film to a vapor deposition section and vapor-depositing an active solvent to form a composite solid electrolyte layer; and (S6) winding and recovering the substrate comprising the composite solid electrolyte layer using a rewinder.

[0017] In the preparation method, the mixed solution of step (S1) may further include at least one selected from the group consisting of a lithium salt, a cross-linking agent and an initiator. Based on 100 parts by weight of a PEO (polyethylene oxide) copolymer, the mixed solution may include 10 to 100 parts by weight, or 10 to 60 parts by weight of a ceramic compound.

[0018] In the vapor deposition of step (S5), the polar solvent is evaporated naturally at room temperature or by heating, so that gas molecules of the polar solvent may be contained on the surface or inside of the polymer chain.

[0019] Meanwhile, in the preparation method, the crosslinkable functional group is bonded to the PEO-based copolymer through an alkylene linker having 0 to 10 carbon atoms or an alkylene oxide linker (wherein the alkylene linker having 0 carbon atoms represents a single bond), and may be selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.

[0020] In a more specific example, the PEO (polyethylene oxide)-based copolymer may be a copolymer containing repeating units of the following Chemical Formulas 1 to 3:

[0021] [Chemical formula 1]

[0022]

[0023] [Chemical formula 2]

[0024]

[0025] [Chemical formula 3]

[0026]

[0027] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms,

[0028] R2 represents a substituent formed by bonding one or more crosslinkable functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group to a polymer chain through an alkylene linker having 0 to 10 carbon atoms or an oxyalkylene linker (wherein an alkylene linker having 0 carbon atoms represents a single bond), and

[0029] l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.

[0030] Furthermore, in the preparation method, a composite solid electrolyte can be prepared in which the gas molecules of the polar solvent are polar compounds and the content of the polar compounds is 0.1 wt % or more and less than 10 wt % based on the total weight of the composite solid electrolyte.

[0031] Meanwhile, the polar solvent may include at least one selected from the group consisting of carbonate compounds and sulfonyl compounds. More specifically, the polar solvent may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane.

[0032] At the same time, the ceramic compound may include at least one selected from the group consisting of lithium lanthanum zirconium oxide (LLZO) compounds, lithium silicon titanium phosphate (LSTP) compounds, lithium lanthanum titanium oxide (LLTO) compounds, lithium aluminum titanium phosphate (LATP) compounds, lithium aluminum germanium phosphate (LAGP) compounds and lithium lanthanum zirconium titanium oxide (LLZTO) compounds.

[0033] Furthermore, in this production method, steps (S1) to (S6) may be performed continuously.

[0034] Meanwhile, according to another embodiment of the present disclosure, a composite solid electrolyte prepared by the method of one embodiment described above is provided. This composite solid electrolyte includes: a polymer comprising a PEO-type copolymer containing a crosslinkable functional group; a ceramic compound; and a polar compound, wherein at least a portion of the crosslinkable functional groups form crosslinks with each other, so that the polymer forms a three-dimensional network structure, and wherein the gaseous polar compound is contained in the three-dimensional network structure or may have a structure bonded to a polymer chain.

[0035] [Beneficial Effects]

[0036] The method for preparing the composite solid electrolyte disclosed in the present invention can prepare the composite solid electrolyte through a continuous process and can be mass-produced.

[0037] In addition, the composite solid electrolyte can maintain the original structural characteristics of the polymer without deforming or destroying the polymer chain, improve the mobility of the polymer chain and make the ceramic particles evenly distributed in the composite solid electrolyte, thereby improving the ionic conductivity of the composite solid electrolyte.

[0038] In addition, the composite solid electrolyte contains a very small amount of gaseous polar solvents (polar compounds) and can thus exhibit improved ionic conductivity and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The present invention is a flow chart of a method for preparing a composite solid electrolyte. DETAILED DESCRIPTION

[0040] Hereinafter, for better understanding of the present disclosure, the present disclosure will be described in more detail.

[0041] The terms or words used in the specification and the appended claims should not be construed as limited to the ordinary or dictionary meanings, but should be interpreted in the present disclosure with meanings and concepts consistent with the technical ideas of the present disclosure based on the principle that the inventor can appropriately define the concepts of the terms to appropriately describe his own invention in the best manner.

[0042] As used herein, the term "polymer film" refers to a film prepared by coating and drying a mixed solution containing a PEO (polyethylene oxide) copolymer containing a cross-linkable functional group and a ceramic compound. Polymer chains containing cross-linked bonds through cross-linkable functional groups are formed inside the polymer film, and the internal space of the polymer chain contains the ceramic compound in a dispersed form.

[0043] As used herein, the term "composite solid electrolyte" refers to an electrolyte having a structure in which a polymer film is vapor-deposited with a polar solvent so that a polar compound, which is a gas molecule of the polar solvent, is contained on the surface or inside of a polymer chain.

[0044] Regarding the term "bond" as used herein, that is, regarding the conformation of a polar compound (vapor-deposited polar solvent) "bonded" to a polymer chain (e.g., a chain of a PEO-based copolymer), the term "bond" broadly refers to a conformation of a gaseous polar compound (which is a polar solvent molecule) that remains fixed to a polymer chain by vapor deposition of a polar solvent. In other words, the "bond" is not limited to a specific type of physical bond, chemical bond, etc., but refers to a state of being fixed by various bonds including physical bonds, chemical bonds, etc., or a state of being simply attached and fixed (e.g., by adsorption, etc.), or a state of being contained in a three-dimensional network structure formed by polymer cross-linking and being located near a polymer chain or a cross-linked structure and fixed.

[0045] As used herein, the term "three-dimensional network structure" is a structure including a three-dimensional framework and an internal space formed by the framework, wherein the framework may include polymer chains including cross-links formed by cross-linkable functional groups, for example, cross-links between cross-linkable functional groups and / or cross-links between cross-linkable functional groups and cross-linking agents. The three-dimensional network structure may also be referred to as a cross-linked structure.

[0046] In the present disclosure, the polar compound exists in a "gaseous state" or is contained in a composite solid electrolyte, indicating that, unlike the case where the polar solvent or the electrolyte containing the polar solvent is injected in a liquid state, the polar compound is deposited in a vapor state, and the polar compound exists in a state different from the liquid-injected electrolyte just after the composite solid electrolyte is prepared or during the charging and discharging process of an all-solid-state secondary battery containing the composite solid electrolyte. However, depending on the storage or operating conditions of the composite solid electrolyte and / or the secondary battery, the vapor-deposited polar compound may have a partially or temporarily liquefied state. Even in this case, the vapor-deposited polar compound exhibits higher mobility than the polar solvent injected in a liquid state, and exhibits a state different from the polar solvent in a liquid state, which can also be considered to be present or contained in the above-mentioned "gaseous state".

[0047] On the other hand, conventionally, in order to improve the ionic conductivity of solid electrolytes, composite solid electrolytes in which ceramic compounds such as oxides are dispersed in a polymer matrix are prepared, however, when oxide-based ceramic particles in the polymer matrix are unevenly distributed or when a highly crystalline polymer such as polyethylene oxide is used as a polymer, such composite solid electrolytes have a problem of reduced ionic conductivity.

[0048] In addition, conventionally, in order to improve the ionic conductivity of the solid electrolyte, the solid electrolyte is immersed in or loaded on a liquid electrolyte or solvent in a liquid state, or the liquid electrolyte or solvent is directly injected into the solid electrolyte in a liquid state. When the liquid electrolyte or solvent is directly added to the solid electrolyte in this way, it has the effect of improving the ionic conductivity of the solid electrolyte, but this is only based on the high ionic conductivity of the liquid itself to improve the ionic conductivity of the solid electrolyte, and the degree of improvement is not sufficient, and a large amount of liquid electrolyte needs to be injected. In other words, since the conduction of lithium ions is achieved by the liquid electrolyte added to the solid electrolyte rather than the inherent physical properties of the solid electrolyte, it is far from improving the physical properties of the solid electrolyte itself. In addition, when the liquid electrolyte or solvent is directly added or injected into the solid electrolyte in liquid form, there is the following problem: due to the undesirable side reaction between the polymer and the liquid phase, the structure of the solid electrolyte collapses, such as the polymer chain is damaged or the polymer internal bond is broken, or the ionic conductivity is reduced.

[0049] In addition, when solvents or liquid electrolytes are directly injected into solid electrolytes, the liquid molecules diffuse rapidly within the solid electrolyte, rapidly causing relaxation of the polymer chains and promoting surface gelation, which may lead to a decrease in mechanical properties, and problems such as liquid leakage of the liquid electrolyte may not be completely solved.

[0050] In addition, Japanese Patent Application Laid-Open No. 1994-124713 as a prior art discloses a technique of vapor-depositing a solvent on a general PEO (polyethylene oxide) polymer. In this case, there is a problem that the internal structure of the polymer collapses and ion conductivity cannot be ensured.

[0051] Therefore, the present inventors prepared a polymer film cross-linked with a PEO (polyethylene oxide)-based copolymer modified with a cross-linkable functional group, wherein during the cross-linking, a ceramic compound was mixed together to ensure that the ceramic compound was uniformly dispersed in the internal space of the polymer chain. In addition, by contacting the polymer film with the vapor of a polar solvent, a very small amount of gas molecules of the polar solvent are bound to the polymer chain or contained in the internal space of the polymer chain.

[0052] The composite solid electrolyte prepared in this manner includes: a polymer comprising a PEO (polyethylene oxide) type copolymer containing cross-linkable functional groups; a ceramic compound; and a polar compound, wherein at least a portion of the cross-linkable functional groups form cross-linked bonds with each other so that the polymer forms a three-dimensional network structure, and wherein the gaseous polar compound is contained in the three-dimensional network structure or can represent a structure bonded to a polymer chain.

[0053] It has been confirmed that the composite solid electrolyte exhibits improved ionic conductivity even when containing trace amounts of polar compounds derived from gaseous polar solvents. This is predicted because gaseous polar compounds affect the physical properties of PEO-based copolymers such as crystallinity and increase the chain mobility of polymer chains, thereby improving the conductivity of lithium ions contained in the solid electrolyte. In addition, this ionic conductivity can be further improved by uniformly dispersing ceramic compounds.

[0054] Furthermore, the present inventors have developed a method for preparing a composite solid electrolyte, which can prepare a composite solid electrolyte exhibiting improved ionic conductivity by a continuous process using the above-mentioned principle, making its large-scale production possible.

[0055] Next, a method for preparing such a composite solid electrolyte will be described in detail.

[0056] Preparation method of composite solid electrolyte

[0057] According to one embodiment of the present invention, a method for preparing a composite solid electrolyte is provided, and an example of a flow chart thereof is shown in Figure 1 middle.

[0058] refer to Figure 1, a method for preparing a composite solid electrolyte of an embodiment comprises the following steps: (S1) preparing a mixed solution comprising a PEO (polyethylene oxide) copolymer containing a crosslinkable functional group and a ceramic compound; (S2) unwinding a substrate using an unwinder and supplying it to a conveying path; (S3) applying the mixed solution to the substrate to form a coating film; (S4) transferring the substrate having the coating film formed thereon to a drying section and drying it to form a polymer film; (S5) transferring the polymer film to a vapor deposition section and vapor-depositing an active solvent to form a composite solid electrolyte layer; and (S6) winding and recovering the substrate comprising the composite solid electrolyte layer using a rewinder. At this time, steps (S1) to (S6) may be performed continuously.

[0059] Hereinafter, a preparation method according to an embodiment will be described in more detail for each step.

[0060] In step (S1), a mixed solution including a PEO (polyethylene oxide)-based copolymer having a cross-linkable functional group and a ceramic compound may be prepared.

[0061] The mixed solution can be prepared by mixing the PEO-type copolymer and the ceramic compound in a solvent, and can also be further prepared by mixing any one or more of a lithium salt, a cross-linking agent and an initiator. The electrolyte can be formed by mixing the lithium salt, and the cross-linking bond of the PEO-type copolymer can be formed when the cross-linking agent and / or the initiator are mixed.

[0062] The solvent is not particularly limited, as long as it is a solvent that can be mixed and dissolved with any one or more of the PEO-based copolymers and lithium salts, crosslinking agents and initiators and can be easily removed by a drying process. For example, the solvent can be acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropanol, dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF) etc. This solvent is a solvent used as a reaction medium for forming a crosslinked bond, and is different from the polar solvents contained in the liquid electrolyte etc., and is completely removed by drying etc. after crosslinking.

[0063] Considering the degree to which the forming process of preparing a composite solid electrolyte can be carried out smoothly, the concentration of the mixed solution can be appropriately adjusted. Specifically, the concentration of the mixed solution can refer to the concentration (weight %) of the polymer in the mixed solution. The concentration of the polymer can be the concentration of the PEO-based copolymer. For example, the concentration of the polymer solution can be 5 weight % to 20 weight %, specifically, it can be more than 5 weight %, more than 7 weight % or more than 9 weight % and less than 13 weight %, less than 17 weight % or less than 20 weight %. If the concentration of the mixed solution is less than 5 weight %, the concentration may be too dilute, and the mechanical strength of the composite solid electrolyte may be reduced, or when applied to a substrate, it may flow downward. If the concentration is greater than 20 weight %, it is difficult to dissolve the lithium salt in the mixed solution at a desired concentration, the viscosity will be high, the solubility will be low, or it may be difficult to apply the lithium salt in the form of a uniform film.

[0064] In addition, the crosslinkable functional group may be composed of two or more. The crosslinkable functional groups may be the same or different from each other, and preferably may be different. When the crosslinkable functional groups are different, a variety of repeating units each containing these functional groups may be included. In addition, when a variety of crosslinkable functional groups are included, the mobility and ionic conductivity of the polymer chain may be more easily controlled.

[0065] The crosslinkable functional group refers to a functional group capable of forming a crosslink bond between crosslinkable functional groups and / or forming a crosslink bond with each other through a crosslinking agent, and may be bonded to the main chain of the polymer chain in the form of a side chain.

[0066] Specifically, the crosslinkable functional group can be directly bonded to the main chain of the PEO-based copolymer, or can be bonded through an alkylene or oxyalkylene linker. Therefore, the crosslinkable functional group can be bonded through an alkylene linker or oxyalkylene linker having 0 to 10 carbon atoms (wherein the alkylene linker having 0 carbon atoms represents a single bond), and can be at least one selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.

[0067] In a more specific example, the PEO-based copolymer containing a cross-linkable functional group may be a copolymer containing repeating units of the following Chemical Formulas 1 to 3:

[0068] [Chemical formula 1]

[0069]

[0070] [Chemical formula 2]

[0071]

[0072] [Chemical formula 3]

[0073]

[0074] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms,

[0075] R2 represents a substituent formed by bonding one or more crosslinkable functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group to a polymer chain through an alkylene linker having 0 to 10 carbon atoms or an oxyalkylene linker (provided that the alkylene linker having 0 carbon atoms represents a single bond), and

[0076] l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.

[0077] For example, the cross-linkable functional group of R2 can form a polymer in the form of a matrix having a three-dimensional network structure formed by cross-linking bonds. The three-dimensional network structure formed by cross-linking bonds can improve the mechanical properties of the composite solid electrolyte, and a gaseous polar compound can be included or bonded in this three-dimensional network structure to provide a composite solid electrolyte with improved ionic conductivity.

[0078] In addition, it is apparent that the PEO-based copolymer may include two or more repeating units of Chemical Formula 3, wherein R2 are cross-linkable functional groups different from each other, and may also include one or more repeating units of Chemical Formula 2.

[0079] When l, m and n are each less than 1, it is difficult to form a polymer due to the small molecular weight, and when l, m and n are each greater than 1000, the solubility during the preparation of the polymer solution decreases due to the increase in viscosity, and the molding for preparing the composite solid electrolyte may become difficult. In particular, when the number of repetitions of the repeating unit containing a crosslinkable functional group in l, m and n of Chemical Formula 3 is greater than 1000, the degree of crosslinking increases excessively, the mobility of the polymer chain may decrease, and the ionic conductivity of the composite solid electrolyte may decrease.

[0080] As used herein, "hydroxy" refers to an -OH group.

[0081] As used herein, "carboxyl" refers to a -COOH group.

[0082] As used herein, "isocyanate" refers to a -N=C=O group.

[0083] As used herein, "nitro" refers to a -NO2 group.

[0084] As used herein, "cyano" refers to a -CN group.

[0085] As used herein, "amide" refers to -C(=O)NR'R", wherein R' and R" can each independently be hydrogen or C1 to C5 alkyl, or R' and R" together with the N atom to which they are attached can form a heterocycle having 4 to 8 carbon atoms in the ring structure.

[0086] As used herein, "amino" may be selected from the group consisting of monoalkylamino, monoarylamino, monoheteroarylamino, dialkylamino, diarylamino, diheteroarylamino, alkylarylamino, alkylheteroarylamino, and arylheteroarylamino, and the carbon number thereof is not particularly limited, but is preferably 1 to 30. Specific examples of amine include methylamino, dimethylamino, ethylamino, diethylamino, phenylamino, naphthylamino, biphenylamino, dibiphenylamino, anthracenylamino, 9-methyl-anthrylamino, diphenylamino, phenylnaphthylamino, ditolylamino, phenyltolylamino, triphenylamino, biphenylnaphthylamino, phenylbiphenylamino, biphenylfluorenylamino, phenyltriphenyleneamino, and biphenyltriphenyleneamino, but are not limited thereto. In addition, "amino" refers to -NH2.

[0087] As used herein, "allyl" refers to a -CH2-CH=CH2 group.

[0088] The weight average molecular weight (Mw) of the copolymer containing chemical formula 1 to 3 can be 100,000g / mol to 2,000,000g / mol, specifically, it can be 100,000g / mol or more, 200,000g / mol or more, or 300,000g / mol or more and 1,600,000g / mol or less, 1,800,000g / mol or less, or 2,000,000g / mol or less. If the weight average molecular weight (Mw) of the copolymer is less than 100,000g / mol, it may not be possible to meet the mechanical properties of the film capable of forming a composite solid electrolyte. If the weight average molecular weight (Mw) of the copolymer is greater than 2,000,000g / mol, the solubility during the preparation of the polymer solution is reduced due to increased viscosity, and the polymer film forming for preparing the composite solid electrolyte may become difficult. In addition, due to the chain mobility caused by the increase in the crystallinity inside the film during polymer film production, the ionic conductivity of the composite solid electrolyte may be reduced. In particular, when the number of repetitions of the repeating unit containing a cross-linkable functional group in l, m, and n is greater than 1000, the degree of cross-linking increases excessively and the mobility of the polymer chain decreases, thereby resulting in a decrease in the ionic conductivity of the composite solid electrolyte.

[0089] Furthermore, the copolymer may be a random copolymer or a block copolymer.

[0090] Meanwhile, the composite solid electrolyte may include a ceramic compound having a lithium ion transport capability to improve the conductivity of lithium ions, and preferably containing lithium atoms but not storing lithium, and having a function of transporting lithium ions, and can improve the ion conductivity of the composite solid electrolyte.

[0091] In addition, in the polymer film formed by the cross-linked bonds induced during drying in step (S4), the ceramic compound can be contained in the internal space of the cross-linked polymer chain in a uniformly dispersed state. The ceramic compound is mixed together in the formation of the mixed solution and can be uniformly dispersed in the internal space between the cross-linked polymer chains without aggregation. This ceramic compound can be beneficial to improve the mechanical strength and ionic conductivity of the composite solid electrolyte due to its uniform dispersion form.

[0092] In addition, the ceramic compound may be in the form of particles. Due to the morphological characteristics of the particles, they may be contained in the composite solid electrolyte in a more uniformly dispersed state. The particles of the ceramic compound may be spherical, and their diameter may be 100 nm to 1000 nm. If the diameter is less than 100 nm, the effect of non-crystallization due to reduced polymer crystallinity may be small, and if the diameter is greater than 1000 nm, the dispersibility may be reduced due to increased aggregation between particles, which may make it difficult to disperse uniformly.

[0093] The ceramic compound may be an oxide or phosphate compound, for example, an oxide solid electrolyte in the form of a lithium metal oxide or a lithium metal phosphate. More specifically, the ceramic compound may be selected from garnet-type lithium lanthanum zirconium oxide (LLZO, Li7La3Zr2O 12 ) compounds, perovskite-type lithium lanthanum titanium oxide (LLTO, Li3xLa 2 / 3-x TiO3) compounds, phosphate NASICON type lithium aluminum titanium phosphate (LATP, Li 1+x Al x Ti 2-x (PO4)3) compounds, lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5 At least one of the group consisting of lithium lanthanum zirconium titanium oxide (LLZTO) compounds. More preferably, at least one oxide solid electrolyte selected from the group consisting of lithium lanthanum zirconium oxide (LLZO), lithium silico-titanium phosphate (LSTP), lithium lanthanum titanium oxide (LLTO), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP) and lithium lanthanum zirconium titanium oxide (LLZTO) can be used.

[0094] Oxide-based solid electrolytes made of oxide or phosphate compounds usually have a high -4 Up to 10 -3 S / cm ionic conductivity value, and has the advantages of being stable in high voltage region, stable in air, and easy to synthesize and handle.

[0095] Therefore, the above-mentioned composite solid electrolyte may further include a ceramic compound to compensate for the disadvantages involved in the polymer-based solid electrolyte.

[0096] In addition, ceramic compounds are not prone to combustion or ignition even at high temperatures above 400°C, so they have high high-temperature stability. Therefore, when the composite solid electrolyte contains a ceramic compound, it can not only improve the mechanical strength of the composite solid electrolyte, but also improve its high-temperature stability and ionic conductivity.

[0097] The ceramic compound may be included in an amount of 10 to 100 parts by weight, or 10 to 60 parts by weight, based on 100 parts by weight of the PEO-based copolymer containing a cross-linkable functional group.

[0098] If the content of the ceramic compound is too small, the effect of reducing the crystallinity of the polymer and making it amorphous caused by the ceramic compound will be reduced, so the effect of improving the ionic conductivity of the composite solid electrolyte is not significant, and the mechanical properties may not reach the expected level due to the formation of the composite material.

[0099] If the content of the ceramic compound is too high, the ceramic compound cannot be uniformly dispersed in the polymer, and the ceramic compound particles may agglomerate and aggregate with each other, thereby preparing a polymer solid electrolyte with reduced ion conductivity.

[0100] In one embodiment of the present disclosure, a lithium salt may be used as a raw material to form an electrolyte. The lithium salt is contained in the internal space between the polymer chains in a dissociated ionic state, and thus the ionic conductivity of the composite solid electrolyte may be improved. At least a portion of the cations and / or anions dissociated from the lithium salt is maintained in a state bonded to the polymer chain and may exhibit mobility during charge / discharge of the battery.

[0101] The lithium salt may include (CF3SO2)2NLi (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, LiC(CF3SO2)3, lithium chloroborane, lower aliphatic carboxylic acid lithium and at least one of the group consisting of lithium tetraphenylborate.

[0102] In addition, based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group, the content of the lithium salt may be 25 to 45 parts by weight. Specifically, the content may be more than 25 parts by weight, more than 30 parts by weight, or more than 35 parts by weight, or less than 40 parts by weight, or less than 45 parts by weight. If the content of the lithium salt is less than 25 parts by weight, the ionic conductivity of the composite solid electrolyte may be reduced, and if the content of the lithium salt exceeds 45 parts by weight, the mechanical strength may be reduced.

[0103] The crosslinking agent can form a crosslinking bond with the crosslinkable functional group, wherein the crosslinking bond can be a hydrogen bond, a bond formed by Lewis acid-base interaction, an ionic bond, a coordination bond, or a bond formed by free radical polymerization.

[0104] The crosslinking agent is not particularly limited as long as it is a multifunctional crosslinking agent that can form a crosslinked bond with a crosslinkable functional group. For example, the crosslinking agent can be selected from trimethylolpropane trimethacrylate, poly(ethylene glycol) diacrylate, poly(ethylene glycol) dimethacrylate, ethylene glycol dimethacrylate (hereinafter referred to as "EGDMA"), 1,3-diisopropenylbenzene (DIP), 1,4-diacryl piperazine, 2-(diethylamino) ethyl methacrylate, 2,6-bisacrylaminopyridine, 3-(acryloyloxy)-2-hydroxypropyl methacrylate, 3,5-bis(acryloylamino) benzoic acid, 3-aminopropyl triethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-methacryloxypropyl trimethoxysilane, bis-(1- (tert-butylperoxy)-1-methylethyl)-benzene, dicumyl peroxide, dimethacrylate, divinylbenzene, malein glycol acrylate, glycidyl methacrylate, hydroxyquinoline, i-phenyldiethoxysilane, malein glycol acrylate, methylenebisacrylamide, N,N'-1,4-phenylenedipropyleneamine, N,O-bisacryloyl-phenylalaninol, N,O-bismethacryloylethanolamine, pentaerythritol triacrylate, phenyltrimethoxysilane, tetramethoxysilane, tetramethylene compounds, tetraethoxysilane and triallyl isocyanurate. One or more polyfunctional crosslinking agents, for example, a difunctional or higher polyvalent compound.

[0105] In addition, the content of the crosslinking agent may be 1 to 30 parts by weight based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group. If the content of the crosslinking agent is less than 1 part by weight, crosslinking with the crosslinkable functional group may not be sufficiently achieved, and if the content of the crosslinking agent is greater than 30 parts by weight, excessive crosslinking may occur and the mobility of the polymer chain may be reduced, resulting in reduced ionic conductivity.

[0106] In one embodiment of the present disclosure, the initiator may induce a free radical polymerization reaction between the crosslinkable functional groups to form a crosslink bond between the crosslinkable functional groups. The functional group capable of free radical polymerization may be a functional group containing a vinyl group at the end, such as an allyl group.

[0107] The initiator is not particularly limited as long as it is an initiator that can induce a free radical polymerization reaction between crosslinkable functional groups. For example, the initiator may include at least one selected from the group consisting of benzoyl peroxide, azobisisobutyronitrile, lauroyl peroxide, cumene hydroperoxide, diisopropylphenyl-hydroperoxide, tert-butyl hydroperoxide, p-methane hydroperoxide and 2,2'-azobis(2-methylpropionitrile).

[0108] Based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group, the initiator may be used in an amount of 0.5 to 2 parts by weight. When the initiator is used within the above range, it may be able to induce a free radical polymerization reaction between the crosslinkable functional groups and effectively form a crosslink bond.

[0109] Meanwhile, in step (S2), the base material may be unwound using an unwinder and supplied to the conveying path.

[0110] The unwinder unwinds and supplies the substrate wound in a roll through a predetermined conveying path, and can unwind and supply the substrate by its own drive. In addition, in step (S6), the substrate can be unwound and supplied by the driving force of the rewinder that winds the substrate on which the composite solid electrolyte layer is formed.

[0111] Therefore, the composite solid electrolyte of one embodiment may be prepared by a roll-to-roll process.

[0112] In addition, there is no particular restriction on the substrate, as long as it can be used as the support of the coating and can be in the form of a film. For example, the substrate can be SUS (stainless steel), polyethylene terephthalate film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, vinyl chloride copolymer film, polyurethane film, ethylene-vinyl acetate film, ethylene-propylene copolymer film, ethylene-ethyl acrylate copolymer film, ethylene-methyl acrylate copolymer film or polyimide film.

[0113] Meanwhile, in step (S3), the mixed solution may be applied to a substrate to form a coating film.

[0114] In addition, the coating method is not particularly limited as long as it can form a coating film by applying the mixed solution to the substrate. For example, the coating method can be rod coating, roller coating, spin coating, slit coating, die coating, blade coating, comma coating, slit die coating, lip coating, spray coating or solution casting.

[0115] In a specific example of the coating method, a solution casting method can be used. More specifically, the mixed solution prepared in step (S1) is placed in a mixer, the mixer is then placed above the substrate, and the mixed solution is continuously cast on the substrate supplied through a unidirectional conveying path to form a coating film.

[0116] Furthermore, in step (S4), the coating film formed on the substrate may be transferred to a drying section and dried to form a polymer film.

[0117] The drying method may use a hot air drying method which uses hot air at a temperature within a certain range for drying, but is not limited to these examples. Any method may be used as long as the coating film on the substrate on which the coating film is formed can be dried.

[0118] Specifically, drying may be performed at 50° C. to 250° C., and specifically, the drying temperature may be 50° C. or more, 70° C. or more, or 90° C. or more and 120° C. or less, 150° C. or less, 200° C. or less, or 250° C. or less. If the drying temperature is lower than 50° C., the coating film formed by applying the mixed solution to the substrate may not be sufficiently dried and may flow down as a liquid phase, and if the drying temperature is higher than 250° C., the coating film applied on the substrate may be damaged or bubbles may be generated, so that a smooth coating film may not be formed.

[0119] Alternatively, the drying may include primary drying and secondary drying. Through the primary drying, a portion of the solvent contained in the coating film can be removed to form a film, and through the secondary drying, crosslinking bonds between crosslinkable functional groups induced by the initiator and / or crosslinking bonds between the crosslinkable functional groups and the crosslinking agent can be formed.

[0120] The primary drying may be performed at room temperature for 5 to 20 hours, and the secondary drying may be performed at 50 to 250° C. as described above. When the drying process is performed by primary drying and secondary drying in this manner, a film having a uniform shape is formed, and internal crosslinking bonds may be better formed.

[0121] In addition, the drying section is not limited to one stage. If the drying path is long, the drying section can be formed in multiple stages to improve the drying efficiency. For example, a drying section of three or more stages can be formed.

[0122] As a result of the drying process, the polymer film undergoes a crosslinking reaction and may include polymer chains containing crosslinks. The crosslinks may include crosslinks between crosslinkable functional groups and / or crosslinks between crosslinkable functional groups and crosslinking agents. For example, at least a portion of the crosslinkable functional groups may form crosslinks with each other via a crosslinking agent, thereby forming the above-mentioned three-dimensional network structure.

[0123] The crosslinking bonds between the crosslinkable functional groups may be urethane crosslinking bonds, ester crosslinking bonds, hydrogen bonds, bonds formed by free radical polymerization of vinyl groups at the ends of allyl groups (-CH2-CH=CH2), etc., but are not limited to these examples.

[0124] Furthermore, the cross-linking bond between the cross-linkable functional group and the cross-linking agent may be a hydrogen bond, a bond formed by Lewis acid-base interaction, an ionic bond, a coordination bond, or a bond formed by free radical polymerization.

[0125] The ceramic compound may be uniformly dispersed in the internal space of the cross-linked polymer chain, for example, in a three-dimensional network structure, and the lithium salt may be dissociated and included in an ion state.

[0126] Meanwhile, in step ( S5 ), the polymer film may be transferred to a vapor deposition section, and an active solvent may be vapor deposited to prepare a composite solid electrolyte.

[0127] Vapor deposition evaporates the polar solvent naturally at room temperature or evaporates it by heating, so that the gas molecules of the polar solvent may be bonded to the polymer chains inside the polymer film, or the gas molecules of the polar solvent may be contained in the internal space of the polymer chains.

[0128] By leaving the polar solvent at room temperature or by heating the vapor-deposited solvent in this way, the polar solvent is uniformly diffused on the surface and / or inside the polymer, so that the gas molecules of the polar solvent can be bonded to the polymer chain or can be contained in the internal space of the polymer chain in a uniformly dispersed form.

[0129] When the polar solvent is placed at room temperature during vapor deposition, a trace amount of the low-boiling-point polar solvent can penetrate into the interior of the solid electrolyte at room temperature, thereby effectively inducing conformational changes in the cross-linked polymer chains within the polymer.

[0130] In addition, when the polar solvent is heated during vapor deposition, the vapor deposition rate can be increased. At this time, the heating temperature is not particularly limited, as long as it is a temperature at which the polar solvent can undergo a phase change into a vapor, for example, it can be 30°C to 80°C. General PEO melts at 60°C, but when a PEO-based copolymer modified with a crosslinkable functional group forms a crosslinked structure, its heat resistance is improved and can withstand up to 80°C, thereby further increasing the vapor deposition rate. In addition, the heating method is not limited, as long as it is a method that can supply energy to generate steam. For example, a direct heating method using a burner or a furnace or an indirect heating method using a heater or a steam pipe, etc., can be used, but the method is not limited to these examples.

[0131] In the heating process, when the heating temperature is too high, there are the following disadvantages: the solvent may boil at a temperature above the boiling point of the polar solvent, or may cause deformation of the polymer, and it is difficult to control the evaporation rate of the polar solvent during the vapor deposition process. Therefore, in order to perform vapor deposition with a trace amount of polar solvent, it may be necessary to perform vapor deposition at a heating temperature within an appropriate range as described above.

[0132] The polymer solid electrolyte containing the polar compound which is a gaseous molecule of a polar solvent bonded to the chain of the cross-linked polymer via vapor deposition or contained in the internal space between the polymer chains may be prepared as described above.

[0133] The polar compound is a gas molecule of a polar solvent used in the vapor deposition process, which can be contained on the surface or inside the polymer chain by adsorbing the gas molecule of the polar solvent onto the polymer during the vapor deposition process and then diffusing it into the polymer chain. Specifically, the polar compound is bonded to the polymer chain or contained in the internal space between the polymer chains in a dispersed form.

[0134] The polar compound is bonded to the polymer chain or contained in the inner space between the polymer chains in a dispersed form, thereby being able to improve the ionic conductivity of the finally prepared composite solid electrolyte.

[0135] This composite solid electrolyte does not contain a liquid solvent or electrolyte, but contains a trace amount of polar compounds, which are contained or bonded in a gaseous state by vapor deposition. This composite solid electrolyte can be confirmed from the following facts: for example, when the electrolyte layer containing the composite solid electrolyte is separated from the all-solid-state battery and then observed with the naked eye or an electron microscope, no liquid component is observed on the surface of the electrolyte layer. In contrast, when a liquid polar solvent or electrolyte is injected into the composite solid electrolyte, a liquid component or a component showing wettability can be observed on the surface of the electrolyte layer. In addition, the composite solid electrolyte in which the polar compound is vapor-deposited and contained in a gaseous state exhibits a significantly higher ionic conductivity than when a liquid polar solvent or electrolyte is injected. Even by comparison of this ionic conductivity, a composite solid electrolyte in which the polar compound is vapor-deposited and contained in a gaseous state can be confirmed.

[0136] Specifically, the polar compound bonded to or contained between the polymer chains can be used as a plasticizer and plasticize the polymer. The plasticized polymer may have an increased amorphous region inside, which can improve the mobility of the polymer chain. As the mobility of the polymer chain increases, the ion hopping effect inside the polymer increases, which can improve the ionic conductivity of the composite solid electrolyte.

[0137] In addition, polar compounds can be used as intermediates for smooth ion transport through ion hopping. Since the affinity between lithium ions and polar compounds is stronger than the affinity between lithium ions and the ether oxygen of PEO-based copolymers, the transmission of lithium ions within the polymer adsorbed with polar compounds may be faster and easier. That is, as the polar compound as a polar solvent molecule flows into the interior of the polymer, the cationic solvation effect of lithium ions increases to improve ion mobility, thereby improving the ionic conductivity of the composite solid electrolyte.

[0138] In addition, the polar solvent or the polar compound corresponding thereto may include at least one selected from the group consisting of carbonate-based compounds and sulfonyl-based compounds.

[0139] Specifically, the polar compound may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane, or a combination thereof.

[0140] Based on the gross weight of the composite solid electrolyte, the content of the polar compound can include more than 0.1 wt % and less than 10 wt %. For example, the content of the polar compound can be more than 0.1 wt %, more than 1 wt % and less than 2 wt %, or less than 8 wt %, or less than 9 wt %, or less than 10 wt %. When the content of the polar compound is less than 0.1 wt %, it is difficult to cause the change of the chain conformation inside the polymer, and therefore, the ionic conductivity of the composite solid electrolyte is not improved. When the content of the polar compound is more than 10 wt %, the composite solid electrolyte has a larger liquid content and has the performance of a semi-solid battery. In addition, due to the gelation of the polymer, the mechanical strength of the composite solid electrolyte may be reduced.

[0141] In addition, in step (S6), the substrate including the composite solid electrolyte layer may be wound and recovered using a rewinder.

[0142] The rewinder may wind up and recover the substrate including the composite solid electrolyte layer into a roll shape, and may wind up the substrate including the composite solid electrolyte layer by its own driving.

[0143] The substrate including the recovered composite solid electrolyte layer may be used as it is, or by further performing a step of separating the composite solid electrolyte layer from the substrate, the composite solid electrolyte may be used in the form of a self-standing film.

[0144] A free-standing film refers to a film which can maintain its film form by itself at room temperature and pressure without a separate support, ie without a substrate.

[0145] In the preparation method of one embodiment described above, steps (S1) to (S6) can be performed continuously, so that the composite solid electrolyte can be prepared by a continuous process.

[0146] Composite solid electrolyte

[0147] The composite solid electrolyte prepared according to one of the above embodiments includes: a polymer comprising a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group; a ceramic compound; and a polar compound, wherein at least a portion of the cross-linkable functional groups of the copolymer form cross-linked bonds with each other, so that the polymer forms a three-dimensional network structure, and wherein the gaseous polar compound is contained in the three-dimensional network structure or may have a structure bonded to the polymer chain.

[0148] In the composite solid electrolyte, the three-dimensional network structure is a structure including a three-dimensional framework and an internal space formed by the upper framework, the framework includes polymer chains containing cross-linked bonds formed by cross-linkable functional groups, and the internal space may contain a ceramic compound or a vapor-deposited gaseous polar compound.

[0149] The cross-linked bonds formed by the cross-linkable functional groups constituting the framework may include cross-linked bonds between the cross-linkable functional groups and / or cross-linked bonds between the cross-linkable functional groups and a cross-linking agent.

[0150] Since the ceramic compound is contained in the internal space of the three-dimensional network structure in a dispersed form, the ceramic compound can be uniformly dispersed. Due to the morphological characteristics of the uniform dispersion of the ceramic compound, the mechanical strength and ionic conductivity of the composite solid electrolyte can be further improved.

[0151] In addition, the gaseous polar compound may be bonded to the polymer chain, or the gaseous polar compound may be contained in the internal space of the polymer chain. At this time, the method of bonding the polar compound to the polymer chain is not particularly limited, as long as the polar compound is fixed to the polymer chain. In other words, the bond may mean a physical and chemical bond and a chemical bond.

[0152] In addition, the form, structure, type and content of the components of the composite solid electrolyte are the same as described above.

[0153] All-solid-state battery

[0154] Another embodiment of the present disclosure also relates to an all-solid-state battery comprising the above-mentioned composite solid electrolyte, wherein the all-solid-state battery includes a negative electrode, a positive electrode and a composite solid electrolyte between the negative electrode and the positive electrode, and the solid electrolyte is prepared according to the above-mentioned one embodiment.

[0155] Specifically, the composite solid electrolyte has a three-dimensional network structure of polymer chains as described above, wherein the ceramic compound is uniformly contained in the internal space of the polymer chains, and the polar compound (which is the gas molecules of the polar solvent) is bonded to the polymer chains or contained in the internal space of the polymer chains through a vapor deposition process, thereby improving the mechanical properties and improving the ionic conductivity, which can be suitable as an electrolyte for an all-solid-state battery.

[0156] Meanwhile, the positive electrode included in the all-solid-state battery includes a positive electrode active material layer, wherein the positive electrode active material layer may be formed on one surface of a positive electrode current collector.

[0157] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.

[0158] In addition, the positive electrode active material is not particularly limited as long as it is a material that can reversibly absorb and desorb lithium ions, and examples thereof may be layered compounds such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v]O2 (wherein M is any one selected from the group consisting of Al, Ga and In, or two or more thereof; and 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1 and x+y+z+v=1), Li (Li a M b-a-b' M' b' ) 2-c A c (wherein 0≤a≤0.2, 0.6≤b≤1, 0≤b'≤0.2 and 0≤c≤0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn and Ti; M' is at least one selected from the group consisting of Al, Mg and B; A is at least one selected from the group consisting of P, F, S and N), or a compound substituted with at least one transition metal; lithium manganese oxide, such as a chemical formula Li 1+y Mn 2-y O4 (where y is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5 and Cu2V2O7; chemical formula LiNi 1-y Ni-type lithium nickel oxide represented by MyO2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M y Lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of Li is replaced by alkaline earth metal ions; disulfides; and composite oxides formed by Fe2(MoO4)3, but are not limited thereto.

[0159] In addition, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material may be 40 to 80 weight %. Specifically, the content of the positive electrode active material may be 40 weight % or more or 50 weight % or more, and 70 weight % or less or 80 weight % or less. If the content of the positive electrode active material is less than 40 weight %, the connectivity and electrical properties between the positive electrode active materials may be insufficient, and if the content of the positive electrode active material is greater than 80 weight %, the mass transfer resistance may increase.

[0160] The binder is a component that assists bonding between the positive electrode active material and the conductive material and bonding with the current collector. The binder may include at least one selected from the group consisting of styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly(vinylidene fluoride)-hexafluoropropylene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.

[0161] In addition, based on the total weight of the positive electrode active material layer, the content of the binder may be 1 wt % to 30 wt %. Specifically, the content of the binder may be 1 wt % or more or 3 wt % or more, and 15 wt % or less or 30 wt % or less. If the content of the binder is less than 1 wt %, the adhesion between the positive electrode active material and the positive electrode current collector may be reduced, and if the content of the binder is greater than 30 wt %, the adhesion is improved, but the content of the positive electrode active material is correspondingly reduced, which may reduce the battery capacity.

[0162] In addition, the conductive material is not particularly limited as long as it does not cause side reactions in the internal environment of the battery and does not cause chemical changes in the all-solid-state battery but has excellent conductivity. The conductive material may generally be graphite or conductive carbon, and may be, for example, but not limited to, one selected from the group consisting of: graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, Denka black, thermal black, channel black, furnace black, lamp black, and summer black; a carbon material having a crystal structure of graphene or graphite; conductive fibers, such as carbon fibers and metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives; and mixtures of two or more thereof.

[0163] Based on the total weight of the positive electrode active material layer, the content of the conductive material can generally be 0.5 wt % to 30 wt %. Specifically, the content of the conductive material can be more than 0.5 wt % or more than 1 wt %, and less than 20 wt % or less than 30 wt %. If the content of the conductive material is too low, i.e., less than 0.5 wt %, it is difficult to obtain the effect of improving conductivity, or the electrochemical characteristics of the battery may deteriorate. If the content of the conductive material is too high, i.e., greater than 30 wt %, the amount of the positive electrode active material is relatively small, so the capacity and energy density may be reduced. There is no particular limitation on the method for introducing the conductive material into the positive electrode, and conventional methods known in the prior art can be used, such as coating on the positive electrode active material.

[0164] In addition, the positive electrode current collector supports the positive electrode active material layer and plays a role in transferring electrons between the external wire and the positive electrode active material layer.

[0165] The positive electrode current collector is not particularly limited as long as it does not cause chemical changes in the all-solid-state battery and has high conductivity. For example, the positive electrode current collector can be made of the following materials: copper, stainless steel, aluminum, nickel, titanium, palladium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy, etc.

[0166] In order to improve the bonding strength with the positive electrode active material layer, the positive electrode current collector may have a fine protrusion and depression structure on its surface or may adopt a three-dimensional porous structure. Thus, the positive electrode current collector may be used in any of various forms, including films, sheets, foils, grids, nets, porous bodies, foams, and non-woven fabric structures.

[0167] The positive electrode as described above can be prepared according to a conventional method. Specifically, the positive electrode can be prepared by the following process: a positive electrode active material layer-forming composition prepared by mixing a positive electrode active material, a conductive material and a binder in an organic solvent is coated on a positive electrode current collector and dried, and the current collector is optionally compression molded to increase the electrode density. At this time, as an organic solvent, it is preferred to use a solvent that can make the positive electrode active material, the binder and the conductive material uniformly dispersed and easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropanol, dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP) and the like can be mentioned.

[0168] On the other hand, the negative electrode included in the all-solid-state battery includes a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.

[0169] The negative electrode active material may include a material capable of reversibly inserting and deinserting lithium (Li + ) material, a material that can react with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.

[0170] Able to reversibly insert and deintercalate lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0171] Preferably, the negative electrode active material may be lithium metal, specifically, may be in the form of a lithium metal film or lithium metal powder.

[0172] The content of the negative electrode active material may be 40 to 80% by weight based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40% by weight or more or 50% by weight or more, and 70% by weight or less or 80% by weight or less. If the content of the negative electrode active material is less than 40% by weight, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if the content of the negative electrode active material is greater than 80% by weight, the mass transfer resistance may increase.

[0173] In addition, the binder is the same as described in the above-mentioned positive electrode active material layer.

[0174] In addition, the conductive material is the same as described in the above-mentioned positive electrode active material layer.

[0175] In addition, the negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has conductivity. For example, the negative electrode current collector can be made of the following materials: copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy, etc. In addition, similar to the positive electrode current collector, the negative electrode current collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabric structures having fine protrusions and depressions formed on their surfaces.

[0176] The preparation method of the negative electrode is not particularly limited, and can be prepared by forming a negative electrode active material layer on the negative electrode current collector using a layer or film formation method commonly used in the art. For example, methods such as compression, coating, and deposition can be used. In addition, the negative electrode of the present disclosure also includes the case where the battery is assembled in a state where there is no lithium film on the negative electrode current collector and then a metal lithium film is formed on the metal plate by initial charging.

[0177] According to yet another embodiment, a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source are provided.

[0178] Here, specific examples of the device may include, but are not limited to: power tools driven by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV) or plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; or power storage systems, etc.

[0179] Preferred embodiments will be given below so that the present invention can be easily understood. However, the following embodiments are only for illustrative purposes, and the scope of the present invention is not limited thereto.

[0180] In the following Examples and Comparative Examples, solid electrolytes including a polymer including a copolymer and an organic solvent were prepared as shown in Table 1 below.

[0181] Example

[0182] Example 1: Preparation of composite solid electrolyte

[0183] Step 1) Preparation of mixed solution

[0184] A polyethylene oxide (PEO)-based copolymer of the following Chemical Formula 1a was prepared:

[0185] [Chemical formula 1a]

[0186]

[0187] Wherein, in chemical formula 1a, R1 is -CH2-O-(CH2-CH2-O) k -CH3, R2 is -CH2-O-CH2-CH=CH2, k is 2, the ratio of l:m:n is 85:13:2, and the weight average molecular weight (Mw) of the copolymer is about 2,000,000 g / mol.

[0188] The copolymer of Chemical Formula 1a has an allyl group bonded through an oxymethylene linker as a crosslinkable functional group.

[0189] The polyethylene oxide copolymer is mixed with acetonitrile as a solvent, trimethylolpropane trimethacrylate as a crosslinking agent, benzoyl peroxide as an initiator, LiTFSI as a lithium salt, and LSTP as a ceramic compound to prepare a mixed solution of the polymer and the ceramic compound, and then stirred for 24 hours using a magnetic bar. At this time, the mixed solution of the polyethylene oxide copolymer and the ceramic compound consists of the following materials: based on 100 parts by weight of the polyethylene oxide copolymer, 20 parts by weight of trimethylolpropane trimethacrylate as a crosslinking agent, 1 part by weight of benzoyl peroxide as an initiator, 36 parts by weight of LiTFSI as a lithium salt, and 40 parts by weight of LSTP as a ceramic compound, wherein the acetonitrile solvent is used so that the concentration of the polyethylene oxide copolymer as a polymer contained in the mixed solution is 11.1% by weight, and the concentration of the polymer, namely the polyethylene oxide copolymer and the ceramic compound, is 14.9% by weight.

[0190] Step 2) Supply of substrate

[0191] A SUS foil as a base film was provided through a unidirectional conveying path using an unwinder.

[0192] Step 3) Film formation

[0193] The mixed solution was placed in a mixer and then coated on a SUS foil, which was a base film supplied from an unwinder through a unidirectional conveying path, by a solution casting method to form a coating film.

[0194] Step 4) Film formation

[0195] The coating film formed on the substrate film supplied through a unidirectional conveying path using an unwinder was transferred to a drying section, first dried at room temperature for 12 hours, and then secondarily dried at 100° C. for 3 hours to prepare a polymer film having a thickness of 200 μm.

[0196] Step 5) Preparation of composite solid electrolyte after vapor deposition

[0197] The polymer film is transported to the vapor deposition section and vapor deposited.

[0198] In the vapor deposition, the lower part of the chamber in the vapor deposition part is filled with EMC (ethyl methyl carbonate) solvent, and then naturally evaporated at room temperature for 72 hours, and the EMC vapor is allowed to flow into the inside of the polymer film transferred to the upper part of the chamber. Therefore, the EMC molecules are bonded to the polymer chains inside the polymer film or deposited to be located in the internal space of the polymer chains to prepare a composite solid electrolyte layer.

[0199] Step 6) Preparation of composite solid electrolyte after vapor deposition

[0200] The substrate film including the prepared composite solid electrolyte layer was wound and recovered using a rewinder. Then, the substrate film was peeled off to prepare a composite solid electrolyte in the form of a self-supporting film.

[0201] Comparative Example:

[0202] Comparative Example 1: Composite solid electrolyte containing only modified PEO (without liquid)

[0203] A composite solid electrolyte was prepared in the same manner as in Example 1, except that the step of vapor depositing the EMC solvent, ie, step 5) of Example 1, was not performed.

[0204] Comparative Example 2: Composite solid electrolyte containing modified PEO + a large amount of liquid

[0205] A composite solid electrolyte was prepared in the same manner as in Example 1, except that the EMC solvent was directly injected into the composite solid electrolyte prepared in step 1) of Example 1.

[0206] Comparative Example 3: Unmodified PEO + ceramic compound + composite solid electrolyte deposited with organic solvent

[0207] A composite solid electrolyte was prepared in the same manner as in Example 1, except that a polyethylene oxide (PEO) homopolymer (weight average molecular weight: about 4,000,000 g / mol) without substituted crosslinkable functional groups was used, and no crosslinking agent or initiator was added.

[0208] Comparative Example 4: Modified PEO + polymer solid electrolyte deposited with organic solvent

[0209] A solid electrolyte was prepared in the same manner as in Example 1, except that no ceramic compound was added.

[0210] Experimental example

[0211] Experimental Example 1: Measurement of polar compound content

[0212] The content of the polar compound can be measured by using a balance and monitoring the weight of the liquid phase evaporated over time when the solid electrolyte sample is heated. For example, it can be measured by monitoring the weight of the liquid phase evaporated over time when the sample is heated at a temperature of 55 to 70°C or 60°C using a heated electronic balance (AND MS-70). When the amount of polar compound evaporated over time reaches saturation, the saturated amount at this time is considered to be the total amount of polar compounds contained in the solid electrolyte. In the embodiments and comparative examples, the polar compound can be ethyl methyl carbonate (EMC).

[0213] Experimental Example 2: Measurement of ionic conductivity of composite (or polymer) solid electrolytes

[0214] In order to measure the ionic conductivity of the composite solid electrolytes prepared in the examples and comparative examples, a 2 A composite solid electrolyte was formed on the lower substrate of a coin cell, and then SUS was used as a blocking electrode to manufacture a coin cell for ion conductivity measurement.

[0215] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C. with an amplitude of 10 mV and a scan range of 1 Hz to 0.1 MHz, and then the ionic conductivity of the polymer solid electrolyte was calculated using the following Equation 1.

[0216] [Equation 1]

[0217]

[0218] Wherein, in Equation 1, σi is the ionic conductivity of the polymer solid electrolyte (S / cm), R is the resistance of the polymer solid electrolyte measured by electrochemical impedance spectroscopy (Ω), L is the thickness of the polymer solid electrolyte (μm), and A refers to the area of ​​the polymer solid electrolyte (cm 2 The solid electrolyte sample used had L = 200 μm, A = 1.7671 cm 2 .

[0219] Table 1 below shows the content of EMC vapor-deposited (or contained) in the composite (or polymer) solid electrolyte and the measurement results of ionic conductivity.

[0220] [Table 1]

[0221]

[0222] Referring to Table 1, it was confirmed that the continuously prepared composite solid electrolyte of the Example exhibited excellent ion conductivity compared with the solid electrolyte of the Comparative Example.

Claims

1. A method for preparing a composite solid electrolyte, the method comprising the following steps: (S1) preparing a mixed solution comprising a PEO (polyethylene oxide) copolymer containing a cross-linkable functional group and a ceramic compound; (S2) unwinding the substrate using an unwinder and supplying it to a conveying path; (S3) applying the mixed solution onto the substrate to form a coating film; (S4) transferring the substrate having the coating film formed thereon to a drying section and drying it to form a polymer film; (S5) transferring the polymer film to a vapor deposition section and vapor-depositing an active solvent to form a composite solid electrolyte layer; and (S6) Winding and recovering the substrate including the composite solid electrolyte layer using a rewinder.

2. The method for preparing a composite solid electrolyte according to claim 1, wherein: The mixed solution of step (S1) further comprises at least one selected from the group consisting of a lithium salt, a cross-linking agent and an initiator.

3. The method for preparing a composite solid electrolyte according to claim 1, wherein: The mixed solution includes 10 to 100 parts by weight of a ceramic compound based on 100 parts by weight of the PEO (polyethylene oxide)-based copolymer.

4. The method for preparing a composite solid electrolyte according to claim 1, wherein: In the vapor deposition of step (S5), the polar solvent is evaporated naturally at room temperature or by heating, so that gas molecules of the polar solvent are contained on the surface or inside of the polymer chain.

5. The method for preparing a composite solid electrolyte according to claim 1, wherein: The crosslinkable functional group is bonded to the PEO-based copolymer through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms, wherein the alkylene linker having 0 carbon atoms represents a single bond, and The cross-linkable functional group is selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.

6. The method for preparing a composite solid electrolyte according to claim 1, wherein: The PEO (polyethylene oxide) copolymer is a copolymer containing repeating units of the following chemical formulas 1 to 3: [Chemical formula 1] [Chemical formula 2] [Chemical formula 3] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms, R2 represents a substituent formed by bonding one or more crosslinkable functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group to a polymer chain through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms, wherein the alkylene linker having 0 carbon atoms represents a single bond, and l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.

7. The method for preparing a composite solid electrolyte according to claim 1, wherein: The gas molecules of the polar solvent are polar compounds, and The content of the polar compound is 0.1 wt % or more and less than 10 wt % based on the total weight of the composite solid electrolyte.

8. The method for preparing a composite solid electrolyte according to claim 1, wherein: The polar solvent includes at least one selected from the group consisting of carbonate compounds and sulfonyl compounds.

9. The method for preparing a composite solid electrolyte according to claim 1, wherein: The polar solvent includes at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane.

10. The method for preparing a composite solid electrolyte according to claim 1, wherein: The ceramic compound includes at least one selected from the group consisting of lithium lanthanum zirconium oxide (LLZO) compounds, lithium silicon titanium phosphate (LSTP) compounds, lithium lanthanum titanium oxide (LLTO) compounds, lithium aluminum titanium phosphate (LATP) compounds, lithium aluminum germanium phosphate (LAGP) compounds and lithium lanthanum zirconium titanium oxide (LLZTO) compounds.

11. The method for preparing a composite solid electrolyte according to claim 1, wherein: Steps (S1) to (S6) are performed continuously. 12 . A composite solid electrolyte prepared by the preparation method according to claim 1 .

13. The composite solid electrolyte according to claim 12, comprising: A polymer comprising a PEO-type copolymer containing a cross-linkable functional group; Ceramic compounds; and Polar compounds, wherein at least a portion of the cross-linkable functional groups form cross-links with each other, so that the polymer forms a three-dimensional network structure, and The polar compound in gaseous state is contained in the three-dimensional network structure or bonded to the polymer chain.